2017
DOI: 10.14238/pi57.1.2017.12-7
|View full text |Cite
|
Sign up to set email alerts
|

Lactate profiles of pediatric shock patients in Cipto Mangunkusumo General Hospital 2015: a pilot study

Abstract: Background The 2015 Surviving Sepsis Campaign (SSC) guidelines for management of shock recommend blood lactate to assess the success of resuscitation in shock. However, a study in adults found that 1/3 of septic shock patients had normal lactate levels (alactatemia) and lower mortality rates. Objective To evaluate lactate profiles, possible factors affecting lactate levels, and mortality outcomes in pediatric shock patients in the emergency room (ER) and pediatric intensive care unit (PICU). Methods This was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 18 publications
2
7
1
Order By: Relevance
“…The majority of patients in this study suffered from septic shock. A similar study conducted in Jakarta also shows the domination of patients with septic shock (8). This is supported by the result of a randomized clinical trial which showed that septic shock is the most common type of shock, followed by hypovolemic shock, cardiogenic shock, and obstructive shock (9).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The majority of patients in this study suffered from septic shock. A similar study conducted in Jakarta also shows the domination of patients with septic shock (8). This is supported by the result of a randomized clinical trial which showed that septic shock is the most common type of shock, followed by hypovolemic shock, cardiogenic shock, and obstructive shock (9).…”
Section: Discussionmentioning
confidence: 68%
“…This study was dominated by patients with alactatemia (blood lactate level being under the pathological range). A study conducted in a general hospital in Jakarta shows a similar result, where in a group of pediatric shock patients most of the lactate blood levels were recorded as normal to low (8). The condition of hyperlactatemia (blood lactate level being above the normal range) has been known as a marker of tissue hypoxia.…”
Section: Discussionmentioning
confidence: 73%
“…Their study demonstrated that only 37% of pediatric shock patients had increased lactate. [ 18 ] A previous study by Scott et al . demonstrated normalization of lactate within 2–4 h of presentation, with decreased risk of persistent organ dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a single-center study in India by Gadappa and Behera reported that shock incidence in a pediatric intensive care unit (PICU) was 8.6% [ 3 ]. According to a retrospective study, septic shock was the most frequent type of shock (51%) among children admitted to the emergency department and the PICU, followed by hypovolemic (38.1%), cardiogenic (6.5%), and other distributive shocks (4.4%) [ 4 ]. This finding was in accordance with the results from De Backer et al [ 5 ].…”
Section: Introductionmentioning
confidence: 99%